Basic statistics for business and economics - Lind, Douglas A.; Marchal, William G.; Wathen, Samuel Adam (McGraw-Hill/Irwin, 2013)
This title provides students majoring in all fields of business administration with an introductory survey of the many applications of descriptive and inferential statistics.